DAYA HIDUP IDENTITAS LOKAL CANDI CANGKUANG DI KAMPUNG PULO GARUT JAWA BARAT - -, Prima Yustana; Sunarmi; Soewarlan, Santoso (TEXTURE Art and Culture Journal, 2024)
Cangkuang Temple is a very unique temple, its uniqueness is found in several elements contained in the name, form and location of the temple. In discussing this article, it is necessary to use an approach that is by the material object and the existing formal object, the material object is discussed using an aesthetic approach while the formal object uses a source interview approach and sees the relevance of the notion of vitality by Dwi Marianto, this approach is used to look deeper into what potential is contained in Cangkuang Temple, Garut, West Java, tourism potential is the main potential supported by its location on a small islandthatcanonlybeaccessedusingbamboorafts.Theresearchmethodusesadescriptive qualitative method based on the potential existence of three exciting things: temples, tombs or tombstones, and traditional villages. The three elements have a solid connection because untilnowthetraditionalvillageorcommonlycalledKampungPulostillmaintainstheprinciples instilled byits ancestors who are familiarly called Mbah Dalem Arif Muhammad